Left Volume Atrial Index and P-wave Dispersion as Predictors of Postoperative Atrial Fibrillation After Coronary Artery Bypass Graft: A Retrospective Cohort Study - Achmad, Chaerul; Tiksnadi, Badai Bhatara; Akbar, Mohammad Rizki; Karwiky, Giky; Sihite, Teddy Arnold; Pramudya, Arsha; Iqbal, Mohammad; Febrianora, Mega (Current problems in cardiology, 2023)
Preoperative left atrial remodeling as Postoperative atrial fibrillation (POAF) predisposing factors could be measured by left atrial volume index (LAVI) and P-wave dispersion. This study aimed to assess P-wave dispersion and LAVI as preoperative predictors of POAF among patients who underwent Coronary Artery Bypass Graft (CABG). An analytical retrospective cohort study was performed on patients who underwent CABG. The P-wave dispersion and POAF were evaluated based on documented ECG results. LAVI size was collected from echocardiographic reports. Hazard ratios of P-wave dispersion and LAVI for POAF were analyzed using Cox proportional hazard model. A total of 42 subjects (57 ± 1 years) were included in this study. POAF occurred in 28.6% of patients at a median of 2 days after CABG. P-wave dispersion was significantly longer in patients in whom AF was developed (53.03 ± 3.82 ms vs 44.01 ± 1.98ms, p:0.028), while LAVI difference was not significant. The Cox proportional hazard model showed a significant association between P-wave dispersion and risk of POAF (HR 1.05, CI95%, 1.001-1.103; P = 0.048). There was no association between LAVI and risk of POAF (HR 1.003, CI 95%, 0.965-1.044; P = 0.864). P-wave dispersion is a predictor of POAF in patients who underwent CABG. Risk stratification using P-wave dispersion enables clinicians to identify high-risk patients before CABG surgery.